On the representation of hierarchical structure: Revisiting Darwin’s musical protolanguage - Miyagawa, Shigeru; Arévalo, Analía; Nóbrega, Vitor A. (Frontiers in Human Neuroscience, 2022)
In this article, we address the tenability of Darwin’s musical protolanguage, arguing that a more compelling evolutionary scenario is one where a prosodic protolanguage is taken to be the preliminary step to represent the hierarchy involved in linguistic structures within a linear auditory signal. We hypothesize that the establishment of a prosodic protolanguage results from an enhancement of a rhythmic system that transformed linear signals into speech prosody, which in turn can mark syntactic hierarchical relations. To develop this claim, we explore the role of prosodic cues on the parsing of syntactic structures, as well as neuroscientific evidence connecting the evolutionary development of music and linguistic capacities. Finally, we entertain the assumption that the capacity to generate hierarchical structure might have developed as part of tool-making in human prehistory, and hence was established prior to the enhancement of a prosodic protolinguistic system.